EDUCATION SECTOR REFORMS AND DEMOGRAPHY: ISSUES AND IMPLICATIONS IN NIGERIA - FASHAGBA, Irewolede; AKINNUBI, Olaolu Paul; ADEOYE, Moses Adeleke (Universitas Ratu Samban, 2025)
The article explores the relationship between demographic factors and the education sector in Nigeria. The research objective is to identify the nature of the population age structure and its implications for educational planning and reforms. The study employs a qualitative research method, utilising secondary data from the 2006 census and relevant literature to analyse demographic trends and their impact on education. Major findings reveal that a significant proportion of children under 18 years have not been accurately counted, leading to resource allocation and educational planning challenges. Furthermore, the research highlights that Nigeria allocates only about 5% of its national budget to education, far below the recommended 26%, exacerbating the sector's challenges. In conclusion, the paper emphasises the critical need for accurate demographic data to inform educational policies and planning. It recommends that the government regularly update population data and align educational content with demographic realities to enhance literacy levels and educational outcomes. By addressing these issues, Nigeria can better meet the educational needs of its growing population and improve overall human development.